2022
DOI: 10.3389/frobt.2022.999392
|View full text |Cite
|
Sign up to set email alerts
|

Mole crab-inspired vertical self-burrowing

Abstract: We present EMBUR—EMerita BUrrowing Robot—the first legged robot inspired by the Pacific mole crab, Emerita analoga, capable of burrowing vertically downward. We choose Emerita analoga as a model organism for its rapid downward burrowing behaviors, as it is four times as fast as the most rapid bivalve mollusk. Vertical burrowing in granular media is a challenging endeavor due to the tendency for the media to create upwards resistive forces on an intruder, even during purely horizontal motions. Our robot is capa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 48 publications
1
9
0
Order By: Relevance
“…This burrowing mechanism is limited to the surface layer of sand; mole crabs generally burrow only deep enough to cover themselves but leave feeding appendages exposed. This is similar to the deepest depths achieved by a mole-crab inspired robot with counter-rotating legs in beads ( Treers et al, 2022 ). Authors suggest that achieving deeper depths may be possible, even in natural soils, with a combination of higher torque actuators, additional fluidization strategies, or local inertial effects.…”
Section: Burrowing Challenge 1: Making Spacesupporting
confidence: 80%
See 1 more Smart Citation
“…This burrowing mechanism is limited to the surface layer of sand; mole crabs generally burrow only deep enough to cover themselves but leave feeding appendages exposed. This is similar to the deepest depths achieved by a mole-crab inspired robot with counter-rotating legs in beads ( Treers et al, 2022 ). Authors suggest that achieving deeper depths may be possible, even in natural soils, with a combination of higher torque actuators, additional fluidization strategies, or local inertial effects.…”
Section: Burrowing Challenge 1: Making Spacesupporting
confidence: 80%
“…Fluidization also is used by rapidly burrowing mole crabs that live in wave-swept sandy beaches; they use rapid movements of their legs to push grains backwards as they quickly burrow down into the sand ( Trueman, 1970 ). Mole crabs have inspired robotic solutions that excavate with legs ( Russell, 2011 ; Teers et al, 2022 ). This burrowing mechanism is limited to the surface layer of sand; mole crabs generally burrow only deep enough to cover themselves but leave feeding appendages exposed.…”
Section: Burrowing Challenge 1: Making Spacementioning
confidence: 99%
“…For this purpose, they use four pairs of legs to scrape the material off the ground. During the digging motion, legs are successively extended or retracted, hence creating motion anisotropy and enabling the body to burrow ( Trueman, 1970 ; Faulkes and Paul, 1997 ; Treers et al., 2022 ). This animal is also suspected of using fluidization, which will be described later.…”
Section: Statics-based Movementsmentioning
confidence: 99%
“…The arms, using an anisotropic motion, are perpendicular to the material while progressing and parallel to the body during the swing phase. In Treers et al. (2022) , a mole crab-inspired robot was built, able to dig itself through the sand by statically moving the sand from below to the top.…”
Section: Statics-based Movementsmentioning
confidence: 99%
“…These various types of movements have inspired the development of robotic systems, including robotic snakes ( Marvi et al, 2014 ) with sidewinding and flipper-driven ( Mazouchova et al, 2013 ) walking on the surface of the granular media. Underneath the surface of granular media, self-burrowing of a mole crab-inspired robot with legs ( Treers et al, 2022 ), burrowing with underactuated appendages resulting in an asymmetric profile between power and return strokes ( Chopra et al, 2023 ), and growing with a root-like robot ( Naclerio et al, 2021 ) all show successful burrowing. More reviews on bioinspired robotic burrowers can be found in ( Wei et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%